Preparation of urea-derived carbon dots and application of urea-derived carbon dots in inhibition of algae and degradation of algal toxins

Urea-derived carbon dots (UDs) prepared through hydrothermal reactions are used to inhibit algae growth and degrade algatoxins, solving the problem of controlling algae blooms and degrading algatoxins in the prior art, and achieving efficient and environmentally friendly algae inhibition and toxin degradation effects.

CN119569039APending Publication Date: 2025-03-07JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411806023.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

Smart Images

  • Figure CN119569039A_ABST
    Figure CN119569039A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of urea-derived carbon dots and application of the urea-derived carbon dots to inhibition of algae and degradation of algal toxins, and belongs to the technical field of nano agricultural regulation and control. Urea is used as a substrate, and urea-derived carbon dots (UDs) are synthesized through a hydrothermal method. The UDs can be used as an inhibitor to inhibit growth of algae cells in lakes, and can also be used as a photocatalyst to generate free radicals to attack the algae cells, so that the oxidative stress level and membrane damage degree of the algae cells are increased to cause death of the algae cells, and microcystic toxins generated by the UDs are degraded at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nano-agricultural regulation, and specifically relates to the preparation of urea-derived carbon dots and their application in inhibiting algae and degrading algal toxins. Background Art

[0002] The uncontrolled reproduction of harmful algae and their toxic metabolites, microcystin (MC-LR), seriously inhibits the growth of aquatic animals, disrupts the balance of aquatic ecosystems, and even threatens human health. Therefore, there is an urgent need to control algal blooms on a global scale. Currently, various physical, chemical, and biological techniques have been developed for controlling algal blooms. Of course, the effectiveness of these methods in curbing algal blooms is undeniable; however, they are also accompanied by some outstanding problems.

[0003] For example, Murray et al. (Murray, D., Jefferson, B., Jarvis, P., Parsons, SA, 2010. Inhibition of three algae species using chemicals released from barleystraw. Environ. Technol. 31, 455-466.) pointed out that chemical methods are costly and can cause secondary pollution. Chemical preparations show rapid and effective efficacy in destroying cell membranes, but they also accelerate the release of algal toxins into aquatic areas, potentially exacerbating environmental hazards. In addition, the use of these chemical agents may inadvertently damage the integrity of the aquatic environment.

[0004] On the other hand, as Sengco et al. (Sengco, MR, 2009. Prevention and control of Karenia brevis blooms. Harmful Algae 8, 623-628.) mentioned: Physical methods require a lot of manpower and physical, and will also affect other aquatic organisms. Physical techniques essentially rely on human intervention and special equipment, which may limit their wide applicability and scalability. In addition, the process of mechanical crushing often leads to the release of algal toxins, causing greater secondary pollution.

[0005] On the other hand, biotechnology mainly relies on aquatic biota and takes a longer time to achieve the desired results, thus increasing the time cost associated with the implementation of biotechnology but affecting the overall ecosystem due to the introduction of other new species.

[0006] Therefore, there is an urgent need to develop environmentally friendly methods that can simultaneously control algal blooms and degrade algal toxins. Summary of the invention

[0007] [Technical issues]

[0008] The invention provides a new way to control / inhibit algae growth and degrade algae toxins, and provides corresponding inhibitor products.

[0009] [Technical solution]

[0010] On the one hand, the present invention provides a method for preparing urea-derived carbon dots, which is prepared directly by hydrothermal reaction using urea as a carbon source.

[0011] In some embodiments, the temperature of the hydrothermal reaction is 180-200°C.

[0012] In some embodiments, the hydrothermal reaction time is 4 to 8 hours.

[0013] In some embodiments, in the hydrothermal reaction, the concentration of urea relative to water is 0.1-1.0 g / mL; specifically, 0.5 g / mL may be selected.

[0014] In some embodiments, the urea-derived carbon dots are evenly distributed and are in the form of spherical particles with an average particle size of 2 to 5 nm.

[0015] In some embodiments, the urea-derived carbon dots contain carbon, nitrogen, and oxygen elements, and the nitrogen content is 4-6 wt %.

[0016] In some embodiments, the urea-derived carbon dots are uniformly distributed and are in the form of spherical particles with an average particle size of 3.4 nm. They include carbon, nitrogen, and oxygen elements, and the N content in the urea-derived carbon dots is 4.13%.

[0017] The present invention prepares a urea-derived carbon dot based on the above method.

[0018] On the other hand, the present invention also provides use of the urea-derived carbon dots in the preparation of cyanobacteria inhibitors.

[0019] In another aspect, the present invention also provides the use of the urea-derived carbon dots in inhibiting the growth of algae.

[0020] Furthermore, the present invention also provides the use of the urea-derived carbon dots in the degradation of algal toxins.

[0021] In some embodiments, the algae comprises cyanobacteria or green algae.

[0022] A method for inhibiting algae growth and degrading algal toxins is to add the urea-derived carbon dots into a water body.

[0023] In some embodiments, UDs can inhibit the growth of Microcystis aeruginosa after entering the water environment, and in the process can also degrade the toxic byproduct microcystins produced by the algae through photocatalysis.

[0024] In some embodiments, the urea-derived carbon dots are used as inhibitors to inhibit the growth of algae cells in lakes; they can also be used as photocatalysts to generate free radicals to attack algae cells, increase the oxidative stress level and membrane damage of algae cells, causing the death of algae cells, and at the same time degrade the microcystins produced by them.

[0025] In some embodiments, the amount of urea-derived carbon dots added to the water body is 24-240 mg / L.

[0026] In some embodiments, after adding the urea-derived carbon dots, the total nitrogen content in the water is 1-10 mg / L.

[0027] In some embodiments, the principle of degradation of algal toxins includes: UDs can reduce the synthesis of chlorophyll through heterogeneous aggregation, produce free radicals (O2 - , ·OH), which induces cell membrane damage through photocatalysis and increases cell membrane permeability, resulting in a significant increase in the extracellular MC-LR content. Under light, the free radicals (O2 - ,·OH) degrades MC-LR by attacking the conjugated double bonds (C4-C5, C6-C7) in MC-LR, among which ·OH has the greatest degradation effect on MC-LR.

[0028] In some embodiments, the water body may be obtained from Taihu Lake (N 31.48220°; E 120.27177°).

[0029] In some embodiments, algae (algae cells) are purchased from the Freshwater Algae Culture Bank of Wuhan Institute of Hydrobiology, China, and are a cyanobacterial model that can secrete microcystins (Microcystis aeruginosa, Microcystis).

[0030] In some embodiments, the initial algae density of the algae cells is 1 to 5*10 6 cell / mL, and the sampling interval was 24h.

[0031] In some embodiments, urea-derivatized carbon dots are formulated into a culture medium for urea-derivatized carbon dots, and then cell culture is performed.

[0032] In some embodiments, increasing the level of free radicals in the culture medium promotes cell death.

[0033] In some embodiments, urea-derived carbon dots have the advantages of small size, high quantum yield, good biocompatibility, low toxicity, high catalytic performance, etc.; and their absorption spectrum is wide, covering the ultraviolet / visible spectrum range to the near-infrared spectrum range, which makes them have broad application prospects in photocatalysis. Under light excitation, urea-derived carbon dots can generate electrons (e - ) and holes (h+ ), these photogenerated charge carriers subsequently generate free radicals through oxidation of water molecules or reduction of oxygen. These free radicals further react with pollutants, mediating the degradation of pollutants.

[0034] [Beneficial Effects]

[0035] The present invention proposes for the first time a urea-derived carbon dot (UDs) synthesized by a hydrothermal method using urea as a substrate. It is further found that the UDs can significantly inhibit the growth of Microcystis aeruginosa and degrade MC-LR. The urea-derived carbon dot UDs of the present invention can inhibit the growth of algae cells and degrade microcystin as a cyanobacteria inhibitor. The inhibition rate of cyanobacteria can reach 78.6%, and the degradation rate of algal toxins can reach 97.7%.

[0036] Furthermore, applying the UDs in water has the following specific effects:

[0037] ①Increase heterogeneous aggregation with algal cells and reduce the photosynthetic pigments in algal cells.

[0038] ②Increase the free radical content in the culture medium, such as O2 - ,·OH, and then attack the algal cells, increasing the ROS level and membrane damage of the algal cells.

[0039] ③ As a photocatalytic material, it generates free radicals to attack microcystin, and two degradation pathways are proposed based on the degradation products:

[0040] Pathway I: Free radicals (O2 - ,·OH) acts as an electrophile to attack the conjugated double bonds (C6 and C7) on the Adda amino acid chain in MC-LR.

[0041] Pathway II: Free radicals oxidize the hydrogen on the conjugated double bonds (C4 and C5) of the Adda amino acid chain in MC-LR. With the generation of free radicals, MC-LR is continuously oxidized, gradually destroying its chemical structure, and finally the CN and CC structures on it are completely destroyed, and UDs achieves complete degradation of MC-LR: urea-derived carbon dots are evenly distributed in spherical particles with an average particle size of 3.4nm, including carbon, nitrogen, and oxygen elements, and the nitrogen content in the urea-derived carbon dots is 4.13%. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Synthesis and characterization of urea-derived carbon dots prepared in Example 1: (A) preparation flow chart of UDs, (B) TEM image of UDs, (C) UV-visible absorption spectrum and fluorescence spectrum of UDs, (D) FTIR spectrum of UDs, high-resolution XPS spectrum of C1s (E) and N1s (F) peaks of UDs, (G) fluorescence lifetime of UDs.

[0043] Figure 2 The urea-derived carbon dots inhibited the growth of algae cells in Example 2: (A) the algae density of Microcystis aeruginosa algae cells under different nitrogen sources (N content: 247.1 mg / L), (B) the growth rate of Microcystis aeruginosa algae cells under different nitrogen sources, (C) the change of the algae density of Microcystis aeruginosa after exposure to UDs (N content: 1, 5, 10 mg / L), (D) the change of the growth inhibition rate of Microcystis aeruginosa algae cells after exposure to UDs (N content: 1, 5, 10 mg / L); (E) the change of algae density in natural water (expressed as OD at 680 nm).

[0044] Figure 3 The mechanism of urea-derived carbon dots inhibiting algal cell growth in Example 3: (A) Inhibition ratio of algal cell fat-soluble chlorophyll and phycobilin content exposed to UDs (N content: 1, 5, 10 mg / L) at environmental concentrations, (B) Laser confocal images showing the level of algal cell membrane damage (right) and oxidative stress (left), (C) SEM image of Microcystis aeruginosa after exposure to UDs, (D) O2 in algal cell culture medium. - , OH and h + strength.

[0045] Figure 4 This is the mechanism by which UDs induce film damage through photocatalysis.

[0046] Figure 5 Photocatalytic degradation of MC-LR by UDs: (A) Absorbance changes of algal cell culture medium at 264 nm; (B) Content of MC-LR inside and outside the cells of Microcystis aeruginosa after exposure to UDs; (C) O2 - , OH and h + Contribution rate to the degradation of microcystins; (D) the content of microcystins in natural water bodies.

[0047] Figure 6 These are two possible pathways for the photodegradation of MC-LR by UDs. DETAILED DESCRIPTION

[0048] The present invention is described in detail below.

[0049] The nitrogen content referred to in the present invention refers to the mass percentage (wt %) of N relative to the total nitrogen source.

[0050] The total nitrogen content involved in the present invention refers to: the concentration of N in the culture medium or water environment, mg / L.

[0051] Example 1: Synthesis and characterization of UDs

[0052] A method for preparing urea-derived carbon dots (UDs), the preparation process is as follows Figure 1 As shown in A, it includes the following steps:

[0053] (1) Dissolve 15 g of urea (available from Shanghai Tianhe Technology Co., Ltd.) in 30 mL of deionized water, and ultrasonicate at 100 kW / h for 15 min to form a mixture after complete dissolution;

[0054] (2) The mixture was transferred to a reactor and reacted at 200°C for 4 h;

[0055] (3) After the reaction is completed, the mixture is cooled and the obtained solution is dialyzed for 72 hours through a dialysis bag with a molecular weight of 500 Da to achieve the purpose of purification. The purified solution is then freeze-dried to obtain urea-derived carbon dots, which are referred to as UDs. The nitrogen content of the urea-derived carbon dots is measured to be 4.13 wt% (i.e., 41.3 mg / g carbon dots).

[0056] like Figure 1 As shown in Figures BG, the prepared UDs are uniformly spherical with an average size of 3.4 nm, which is consistent with the particle size range of CDs (<10 nm), indicating that the urea-derived carbon dots were successfully prepared. The optimal excitation wavelength of UDs is 300 nm, and the optimal emission wavelength is 408 nm. These results show that UDs have a small size and fluorescence properties similar to CDs. XPS further confirmed the presence of C, O, and N elements in the structural composition of UDs, indicating that N is successfully retained in the structure of UDs. N doping changes the local electronic structure of CDs, reduces the internal energy traps between sp2 domains, suppresses non-radiative quenching, greatly enhances the binding of CDs to ions, and improves the photoluminescence quantum yield of CDs. In addition, the fluorescence lifetime of UDs is 3.1 ns, which is longer than that of previously reported CDs (1.42-1.6 ns). Therefore, UDs have good electron transfer ability, which can change their electronic structure, increase the absorbance of the material in the visible light region, and improve the generation of excited states by enhancing the light capture of the material.

[0057] Example 2: Application of UDs as inhibitors to inhibit algal cell growth

[0058] The cyanobacterial model (Microcystis aeruginosa, Microcystis, Microcystis aeruginosa FACHB-315) that secretes microcystin was purchased from the freshwater algae culture bank of the Institute of Hydrobiology, Wuhan, China. The culture was carried out using BG11 medium with a pH of 7.0. The experimental conditions were: ambient temperature 25±1℃, light intensity 12h (1620Lm), and dark cycle culture for 12h.

[0059] Preparation of nitrogen-free culture medium: According to the formula of BG11 culture medium, the nitrogen-containing components are removed to prepare the corresponding nitrogen-free culture medium.

[0060] The specific inhibition experiment is as follows:

[0061] Experiment 1: In the high concentration exposure experiment, algae cells were collected in the logarithmic growth phase and cultured in nitrogen-free medium for 5 days to consume nitrogen in the cells. The algae cells were inoculated in a 250 ml conical flask, and the concentration of NaNO3 in the normal BG11 medium was used as the standard concentration of nitrogen source in the medium. - (NaNO3, Sinopharm Chemical Reagent Co., Ltd.), NH4 + (NH4Cl, Sinopharm Chemical Reagent Co., Ltd.), and UDs materials with the same nitrogen content were used to culture algal cells. The total amount of algal liquid was 100 mL, and the initial algal density was 1.0×10 6 cells / mL. The algal cell suspension was shaken every 12 h and sampled every 24 h. The algal cell density was measured by microscopic counting at 24, 48, 72, and 96 h of exposure; in the environmentally relevant N concentration exposure experiment, BG11 was diluted 10 times as a medium to simulate natural water bodies.

[0062] Experiment 2: Microcystis aeruginosa was placed in nitrogen-free medium containing different concentrations of UDs. The total nitrogen content in the medium was 1, 5, and 10 mg / L (the nitrogen content in UDs was 4.13 wt%, corresponding to the addition of UDs of 24 mg / L, 120 mg / L, and 240 mg / L, respectively). The nitrogen-free medium was used as the control (CK). UDs were pre-suspended in the medium for exposure experiments. The initial cyanobacterial density was 1×10 6 The algal cell suspension was shaken every 12 hours and sampled every 24 hours. The algal cell density was measured by flow cytometry at 24, 48, 72 and 96 hours.

[0063] Experiment 3: Natural water was taken from Taihu Lake (Wuxi City, Jiangsu Province, China, N 31.48220°; E 120.27177°) to verify the inhibitory effect of UDs on algal blooms in natural water. The natural water was filtered with a 0.45 μm filter membrane, sterilized at 121°C for 30 min, and then cultured with algae. Specifically, Microcystis aeruginosa was placed in natural water containing different concentrations of UDs. The UDs concentration used was 240 mg / L (i.e., the total nitrogen content in the water was 10 mg / L), and natural water was used as a control. The initial algae density was 1×10 6 cells / mL, volume 100mL. Shake the algae cell suspension every 12 hours and take samples every 24 hours. Measure the algae cell density in natural water at 24, 48, 72 and 96 hours.

[0064] The density change and inhibition rate of algae cells obtained from the above experiments were measured respectively. The results are as follows: Figure 2 The study found that:

[0065] From Experiment 1, we can see that NO3- -N is conducive to the growth of Microcystis aeruginosa. The overproduction of cyanobacterial cells will eventually lead to the occurrence of cyanobacterial blooms. However, NH4 + and UDs inhibited the growth of Microcystis aeruginosa cells.

[0066] In Experiment 2, the growth rate of algae cells exposed to UDs with total nitrogen content of 1, 5, and 10 mg / L gradually decreased with the increase of concentration, and the inhibition rates of the three treatment groups were 63.3%, 75.2%, and 78.6%, respectively. (Inhibition rate = (algae density of treatment group - algae density of CK treatment group) / algae density of CK treatment group * 100%)

[0067] In addition, it can be seen from Experiment 3 that the algal cell density in natural water bodies after exposure to UDs also decreased significantly within 96 hours.

[0068] Example 3: Mechanism of UDs inhibiting algal cell growth

[0069] The algae cells treated in Experiment 2 of Example 2 were collected respectively, and the photosynthetic pigments were measured, SEM scanning electron microscope photos were taken, the algae cell membrane damage and oxidative stress levels were evaluated, and the O2 - , OH and h + The intensity determines whether cells are attacked by exogenous free radicals.

[0070] The results are as follows Figure 3 , as shown in 4.

[0071] The study found that:

[0072] Compared with the control (CK), the contents of fat-soluble chlorophylls (chlorophyll a (Chl a) and β-carotene (Car)) and phycochlorophyll (phycoerythrin (PE), phycocyanin (PC) and allophycocyanin (APC)) decreased by 73.3%, 74.2%, 72.5%, 79.5% and 78.5%, respectively, after UDs (total nitrogen content in the culture medium was 10 mg / L) treatment, resulting in low light capture, limiting the energy supply for algal cell growth, and thus inhibiting the proliferation of algal cells.

[0073] In addition, UDs exposure caused damage to the algal cell membrane and increased ROS levels. The ROS level of Microcystis aeruginosa cells treated with UDs was 52% higher than that of the control group, and the cell membrane was severely damaged. After exposure to UDs, malondialdehyde (MDA) in the algal cells increased significantly, reflecting the enhanced level of lipid peroxidation in Microcystis aeruginosa. SEM images also showed obvious heterogeneous aggregation between algal cells and UDs. UDs attached to the cell surface may have a shading effect, reducing light capture by algal cells and / or reducing the transport or absorption of substances by cells through the cell membrane. Compared with CK, after exposure to UDs, O2- The signal intensity of ·OH increased significantly, indicating that UDs increased the generation of free radicals in the culture medium. + The signal strength is the opposite. The higher the peak signal strength, the higher the h + The lower the generation, the higher the + The generation of UDs also increases. The valence band (VB) and band gap energy of UDs are 1.0 eV and 3.6 eV, respectively. Photoactivated electrons can reduce oxygen to form photoinduced holes, which then decompose through HV to form hydrogen peroxide and produce hydroxyl radicals. Therefore, UDs can generate electron-hole pairs under light energy excitation, and then generate free radicals, causing damage to algal cells and inhibiting algal blooms.

[0074] Example 4: Photocatalytic degradation of algae toxins using UDs

[0075] Experiment A: Microcystis aeruginosa was placed in nitrogen-free medium containing different concentrations of UDs. The total nitrogen content in the medium was 1, 5, and 10 mg / L (the nitrogen content in UDs was 4.13 wt%, corresponding to the addition of UDs of 24 mg / L, 120 mg / L, and 240 mg / L, respectively). The nitrogen-free medium was used as the control (CK). UDs were pre-suspended in the medium for exposure experiments. The initial cyanobacterial density was 1×10 6 cells / mL, volume 100mL. Shake the algal cell suspension every 12 hours and take samples every 24 hours. OD 264 The value was determined, the content of intracellular and extracellular algal toxin (MC-LR) of Microcystis aeruginosa was determined, and the degradation rate of MC-LR was calculated.

[0076] Experiment B: Natural water was taken from Taihu Lake (Wuxi City, Jiangsu Province, China, N 31.48220°; E 120.27177°) to verify the inhibitory effect of UDs on algal blooms in natural water. The natural water was filtered with a 0.45 μm filter membrane, sterilized at 121°C for 30 min, and then cultured with algae. Specifically, Microcystis aeruginosa was placed in natural water containing different concentrations of UDs. The UDs concentration used was 240 mg / L (i.e., the total nitrogen content in the water was 10 mg / L), and natural water was used as a control. The initial cyanobacteria density was 1×10 6 cells / mL, the volume is 100mL. Shake the algal cell suspension every 12 hours and take samples every 24 hours. At 24, 48, 72 and 96 hours, measure the algal toxin content in natural water and calculate the degradation rate of MC-LR.

[0077] The degradation rate of MC-LR = (the content of algae toxins in the CK treatment group - the content of algae toxins in the treatment group) / the content of algae toxins in the CK treatment group * 100%.

[0078] The results are as follows Figure 5shown.

[0079] The experiment found that the OD of Microcystis aeruginosa after UDs treatment 264 The increase, combined with the support of the elevated electrolyte leakage rate (EL) of algal cells, confirmed that UDs indeed increased the membrane permeability of algal cells, leading to the leakage of organic matter and electrolytes and the release of MC-LR from the intracellular to the extracellular space.

[0080] Since UDs can act as photocatalysts to generate free radicals, Experiment A found that after 96 hours of exposure to UDs, the degradation rate of MC-LR reached 97.7%. By comparing the content of microcystin after quenching free radicals, it was found that ·OH played a major role in the degradation process. The degradation performance of UDs in natural water was then tested (Experiment B). After 96 hours of exposure, the content of MC-LR in natural water decreased by 27.5%.

[0081] Based on the LC-MS / MS results, the applicants inferred two possible pathways for UDs to degrade MC-LR. Figure 6 shown.

[0082] Pathway I: Free radicals generated by UDs (O2 - ,·OH) as an electrophile to attack the conjugated double bonds (C6 and C7) on the Adda amino acid chain of MC-LR, thereby isomerizing it to an intermediate with a molecular mass of 1030.1. Subsequently, due to the breakage of the CC bond, MC-LR is oxidized into two intermediates, each containing a ketone and a carboxyl group, with m / z values ​​of 835.2 and 207.0, respectively. Arg and Mdha amino acids are oxidized in the intermediate with an m / z value of 835.2 to form an initial intermediate with an m / z value of 746.6. This process is accompanied by further oxidation and gradual decarboxylation, generating two new intermediates with m / z values ​​of 697.7 and 653.2, respectively. Under the further oxidation of free radicals, the intermediate undergoes decarboxylation of Glu amino acids or decarboxylation of mep amino acids to form two different intermediates with an m / z value of 610.2. Subsequently, these two intermediates undergo decarboxylation of MeAsp amino acids or Glu amino acids to form intermediates with the same structure and molecular weight of 565.6. The intermediate is oxidized by free radicals to form an intermediate with m / z of 526.4, which then undergoes a decarboxylation and deamination process to form two by-products (aldehydes, m / z=482.3) with the same molecular weight but different structures.

[0083] Pathway II: Free radicals oxidize the hydrogen on the conjugated double bonds (C4 and C5) in the Adda amino acid chain of MC-LR to form an intermediate (m / z = 1029.5), and then the C4 and C5 bonds are broken to form two intermediates with m / z of 797.6 and 230.3, respectively. Since the intermediate (m / z = 797.6) contains an aldehyde group, a carboxyl group is formed under the action of free radical oxidation, the molecular weight of the intermediate increases (m / z = 814.6), and two intermediates with different structures (m / z = 828.6) are generated, and ArgMeAsp or ha-ala peptide bond is broken. These two intermediates are hydrolyzed into acids, forming two intermediates with molecular weights of 517.9 and 331.2, respectively. The intermediate (m / z = 517.9) is hydrogenated into an intermediate (m / z = 551.5), which is finally degraded into a product (acid, m / z = 445.1). These results indicate that UDs can exert their photocatalytic degradation function by attacking C4-C5 or C6-C7 in the Adda amino acid on MC-LR. With the generation of free radicals, MC-LR is continuously oxidized, gradually destroying its chemical structure, and finally the CN and CC structures on it are completely destroyed, and UDs achieve complete degradation of MC-LR.

[0084] Comparative Example 1

[0085] Referring to Example 1, the carbon source was replaced with other components to obtain the corresponding carbon dots.

[0086] Microcystis aeruginosa was placed in a nitrogen-free medium containing 240 mg / L carbon dots, and the nitrogen-free medium was used as the control (CK). The carbon dots were pre-suspended in the medium for exposure experiments. The initial cyanobacterial density was 1×10 6 cells / mL, with a volume of 100 mL. The algal cell suspension was shaken every 12 hours and sampled every 24 hours. At 24, 48, 72, and 96 hours, the algal cell density was measured by flow cytometry, and the algal cell growth inhibition rate was calculated; and the degradation rate of MC-LR after a total exposure of 96 hours was measured. The results are shown in Table 1.

[0087] Table 1

[0088]

[0089] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing urea-derived carbon dots, characterized in that: It is directly prepared by hydrothermal reaction using urea as carbon source.

2. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 180-200°C.

3. The preparation method according to claim 1, characterized in that: The hydrothermal reaction time is 4 to 8 hours.

4. The preparation method according to claim 1, characterized in that: In the hydrothermal reaction, the concentration of urea relative to water is 0.1-1.0 g / mL.

5. The preparation method according to claim 1, characterized in that: In the hydrothermal reaction, the concentration of urea relative to water was 0.5 g / mL.

6. A urea-derived carbon dot prepared by the method according to any one of claims 1 to 5.

7. The urea-derived carbon dots according to claim 6, characterized in that: The urea-derived carbon dots are evenly distributed and are in the form of spherical particles with an average particle size of 2 to 5 nm.

8. The urea-derived carbon dots method according to claim 6, characterized in that: The urea-derived carbon dots contain carbon, nitrogen and oxygen elements, and the nitrogen content is 4-6 wt %.

9. The urea-derived carbon dots according to claim 6, characterized in that: The urea-derived carbon dots are evenly distributed and are in the form of spherical particles with an average particle size of 3.4 nm. They include carbon, nitrogen, and oxygen elements, and the nitrogen content of the urea-derived carbon dots is 4.13%.

10. Use of the urea-derived carbon dots according to any one of claims 6 to 9 in the preparation of cyanobacteria inhibitors.

11. Use of the urea-derived carbon dots according to any one of claims 6 to 9 in inhibiting the growth of algae.

12. The use according to claim 11, characterized in that: The algae include cyanobacteria or green algae.

13. Use of the urea-derived carbon dots according to any one of claims 6 to 9 in degrading algal toxins.

14. A method for inhibiting algae growth and degrading algal toxins, comprising adding the urea-derived carbon dots described in any one of claims 6 to 9 into a water body to be treated.

15. The method according to claim 14, characterized in that The amount of urea-derived carbon dots added to the water body is 24-240 mg / L.

16. The method according to claim 14, characterized in that After adding the above urea-derived carbon dots, the total nitrogen content in the water body is 1 to 10 mg / L.